The Strategy of Turmeric and Ginger Farmers at Pasrujambe Village During the Covid-19 Pandemic - Sugiharto, Mochamad Aan; Sazjiyah, Siti Rofiatul (Department of Sociology, Universitas Nasional (Indonesia), 2020)
This study aims at finding out the attempts of turmeric and ginger farmers at Pasrujambe village of Senduro sub-district in Lumajang Regency during COVID-19 pandemic that has a severe impact on every sector, including spices market. The pandemic has caused a significant decrease in spices price. Therefore, the farmers need to make some strategies and changes to adapt to the current situation that result in their profit decrease due to the COVID-19 pandemic. This study applied the AGIL Talcot Parson theory to analyze the interview and observation data result from several farmers as the subject of the study. The analysis result shows that farmers have developed a new method to process turmeric and ginger into tea product as an alternative healthy drink that is considered suitable for the current market related to the pandemic situation. Keywords : Covid-19, farmer, price, spices